PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS VII DI SMP NEGERI 9 PEMATANGSIANTAR - Eunike Juliani Lestari Sitanggang; Lois Oinike Tambunan; Golda Novatrasio Sauduran (Universitas Islam Sumatera Utara, 2022)
This study aims to determine whether there is an effect of the Contextual Teaching and Learning model on the mathematical reasoning abilities of seventh-grade students at SMP Negeri 9 Pematangsiantar. The method used in this research is an experimental method using a True Experimental Design in the form of a Pretest-Posttest Control Design. The sample consisted of two classes, namely the experimental class which was treated with the Contextual Teaching and Learning learning model, and the control class which was given the conventional learning model, each sample group totaling 32 people. Data were collected by observation, test, and documentation methods. Analysis of the data used is using normality test, homogeneity test, and hypothesis testing. The results of hypothesis testing indicate that there is an effect of the Contextual Teaching and Learning learning model on the mathematical reasoning abilities of seventh-grade students at SMP Negeri 9 Pematangsiantar.